The effect of basic trauma and cardiac life support training in increasing the competence of emergency room nurses - Anisha Calista Prakoeswa; Fitri Arofiati; Nur Hidayah (Jurnal Ners, 2022)
Introduction: Nurses on duty in the emergency room (ER) play an important role in the early identification of a life-threatening patient condition, immediate action, and the subsequent care of critically ill patients. Continuous training and improvement need to be done to improve the ER nurses’ competency. This research aimed to analyze the differences in nurses’ competencies. Methods: This quantitative study employed a quasi-experiment design. The sample size comprised 50 nurses of ER in Surabaya with a total sampling technique. Variables used on this study were demographical data as the independent variables and dependent variables including knowledge, attitude and skills. Intervention was given by two methods, online training for knowledge and attitude, while offline training for skill improvement. After ensuring the distribution and homogeneity of the data, a paired t-test was employed for parametric statistical data analysis. Results: There were differences in pre-test and post-test scores in the domain of knowledge, attitude and skill (p = 0.000), respectively. The mean of knowledge, attitude, and skills had increased significantly. Hence, the training is proven to improve those competencies as well as the sub-topic items. Conclusions: Basic Trauma and Cardiac Life Support (BTCLS) training has improved nurse competency; it is advised to hold this training, especially in the ER. Indeed, it can improve healthcare services quality and improve patient safety at health facility. In addition, future research can modify the training time, training delivery methods, and content of BTCLS training materials to adjust with the current situation of the COVID-19 pandemic.